AMORIS LAETITIA AND CONSCIENCE - Curran, Charles E (Asian Horizons, 2016)
This article discusses Amoris laetitia and conscience in light of chapter 8 of the pastoral exhortation dealing with integrating divorced and remarried Catholics more fully into the Catholic Church. The primary focus of the article is on the possibility of communion for some divorced and remarried Catholics. The essay develops in three parts —the remote context beginning 50 years ago involving the pertinent literature on participation of some divorced and remarried Catholics in the Eucharistic banquet based on the decision of conscience in the internal forum; the present context referring to earlier statements by Pope Francis and the two Synods of 2014 and 2015; and finally Amoris laetitia itself. Amoris laetitia insists on the central role of conscience in decisions made by individuals who because of psychological or sociological circumstances cannot now fulfil the objective demands of the norm or law. Pope Francis in Amoris laetitia, however, does not explicitly accept or even mention the specific issue of communion for some divorced and remarried; however, there are indications that Pope Francis himself favours the possibility of Communion for some divorced and remarried. Meanwhile, he is obviously content to live with the doubts, differences, and even confusion about this issue in the life of the Church.